Analisis kesulitan mahasiswa pada mata kuliah sejarah matematika - Warmi, Attin; Adirakasiwi, Alpha Galih (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2018)
This research aims to analyze studentsâ€™ difficulties types and its factors in Mathematics History subject. This research is descriptive qualitative. Research subject of this research consists of six students in second semester of Mathematics department at the FKIP Unsika. Technique of data collection are interview and documentation. Moreover, technique of data analysis through three activities: data reduction, data display, and data conclusion. The result of this research shows students experienced difficulties, firstly comprehending concept difficulties that covers: (1) difficulty on formulating technique or a manner of numeral statement; (2) difficulty differentiate characteristic or symbol form and numerical in Babylonia era, Egypt, Greek and China; (3) difficulty in calculating phase; (4) difficulty applying Pythagoras theorem. Secondly difficulty to communicate that covers: (1) difficulty illustrating and composing of written and numbered form (2) difficulty explaining history of finding number and numerical in order form. Factors cause difficulties, first intrinsic factor: lack of learning activity, difficulty in memorizing numerical symbol and number, difficulty retell story of history development which has been learned. Second extrinsic factor, tend to more active in outside classroom activity.Â Key words: learning difficulty, difficulties factor, history of Mathematics